EFEKTIVITAS TERAPI BEKAM SUNNAH TERHADAP KADAR GULA DARAH SEWAKTU PADA PENDERITA DIABETES MELITUS RUMAH PERAWATAN LUKA STOMA INKONTINENSIA - Rizal Mustakim; Suriadi Suriadi; Lestari Makmuriana (Sekolah Tinggi Ilmu Keperawatan Muhammadiyah Pontianak, 2022)
THE EFFECTIVENESS OF SUNNAH CUPPING THERAPY ON BLOOD SUGAR LEVELS IN DIABETES MELLITUS PATIENTS IN CLINNIC OF WOUNDS, STOMA, & INCONTINENCE SAHABAT CARE PONTIANAK WEST KALIMANTAN Abstract Background: Diabetes mellitus is characterized by hyperglycemia, which is a condition that shows an increase in glucose levels in the blood. Sunnah cupping is a method of treatment by removing blood contaminated with toxins or oxidants from the body through the skin surface with cupping points prescribed by the Prophet Muhammad at a time determined by the Prophet SAW as well. However, in Indonesia there has never been a study that looked at the effectiveness between cupping during the Sunnah and cupping outside the Sunnah. Objective: To observe and analyze the effectiveness of Sunnah cupping on blood sugar levels in patients with diabetes mellitus at the “Sahabat Care” Clinic of Wounds, Stoma & Incontinence, Pontianak. Methods: This research is a quasi-experimental design research with the type of